Methodological component in the content of teaching the grammatical side of foreign language speech (Journal of Universal Science Research, 2023)
This article considers methodological component in the content of teaching the grammatical side of foreign language speech at the university. The goals of teaching a foreign language are an important methodological category. The starting point in determining the strategic goal of education is the social order of society in relation to the younger generation.